Study on the role of calmodulin in sperm function through the enrichment and identification of calmodulin‐binding proteins in bovine ejaculated spermatozoa. Issue 6 (6th January 2020) - Leclerc, Pierre; Goupil, Serge; Rioux, Jean‐François; Lavoie‐Ouellet, Camille; Clark, Marie‐Ève; Ruiz, Juliana; Saindon, Andrée‐Anne
Abstract: Calmodulin is a small, highly conserved acidic protein present at high levels in spermatozoa that mediates numerous intracellular Ca 2+ ‐dependent events. Sperm motility and fertilizing ability results from an array of biochemical pathways under Ca 2+ control, in which the importance of calmodulin is not fully understood. The role of calmodulin in sperm function has been mostly assessed using antagonists. Nevertheless, few known calmodulin‐regulated enzymes have been described in spermatozoa regarding their involvement in sperm function. To further understand the role of this important Ca 2+ mediator in spermatozoa, different studies were also undertaken to investigate and to identify sperm calmodulin‐binding proteins and determine their localization and subcellular distribution as an attempt to elucidate the role of this important Ca 2+ mediator. In the present study, sperm calmodulin‐binding proteins were identified by mass spectrometry after Ca 2+ ‐dependent biotinylated‐calmodulin binding on sperm head proteins subjected to 2D electrophoresis and transferred on a polyvinylidene difluoride membrane. Calmodulin binding protein identification was also done on detergent extracted whole sperm proteins pulled down in a Ca 2+ ‐dependent manner by calmodulin‐conjugated sepharose beads. In this latter group, 300 proteins were identified in at least two experiments out of three, and those identified in the three independent experiments were analyzed for overrepresented biological processes using the Bos taurus Gene Ontology database. Proteins with known function in reproductive processes, fertilization, sperm‐egg recognition, sperm binding to the zona pellucida, regulation of sperm capacitation, and sperm motility were identified and further emphasize the importance of calmodulin in sperm function. Abstract : Calcium‐dependent calmodulin‐binding proteins were pulled down from bull sperm extract by calmodulin‐conjugated sepharose beads and were identified by mass spectrometry. PANTHER overrepresentation test reveals enrichment in proteins with known functions in reproductive processes, fertilization, sperm‐egg recognition, sperm binding to the zona pellucida, regulation of sperm capacitation, and sperm motility.